IMPLEMENTASI KEBIJAKAN KULIAH DARING DI UNIVERSITAS DIPONEGORO - Afta Kartika; Kismartini Kismartini; Amni Zarkasyi Rahman (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
The sprawl covid-19 pandemic that is spreading and difficult to control has made college in the red zone covid-19 and affected areas mandatory online lecture. Diponegoro university rector issued a bill of rector number 20 / un.7. P/ se /2020 asa basis for the implementation of online college and subsequent release of letter number 23/ un7. P/ se /2020 as standard operating procedure (SOP) in implementing online lectures at diponegoro (undip). In the online college implementation using two platforms Ms. Brushes and undip. The purpose of the study is to analyze the implementation of online lectures at diponegoro university and analyze the host factors from the implementation of online lectures at diponegoro university. The study employed a decadent qualitative study method, attributing the informer to the custodian method of sampling and snowball sampling. Although the implementation of online lectures at diponegoro university is consistent with the established standard procedure (SOP), it is not going to be a success, because student LPS is not offset by student competence by its scientific discipline. That is because in the implementation of online lectures at diponegoro university, they still meet some obstacles that are a hindrance to learning achievement. A deterrent factor in the implementation of online college at diponegoro university is internal and external factors